2021
DOI: 10.1186/s12874-021-01233-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical and methodological characteristics of early COVID-19 treatment clinical trials: so much work, so many lost opportunities

Abstract: Background The COVID-19 pandemic continues to rage on, and clinical research has been promoted worldwide. We aimed to assess the clinical and methodological characteristics of treatment clinical trials that have been set forth as an early response to the COVID-19 pandemic. Methods First, we reviewed all registered clinical trials on COVID-19. The World Health Organization International Trials Registry Platform and national trial registries were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Unmeasured confounders and residual confounding may lead to incorrect conclusions (85). Further points of criticism comprise poor quality of study reporting according to the guidelines of reporting observational studies [STROBE; (86)], or failure to include key clinical endpoints such as mortality or hospitalization duration as primary endpoints (87). Only large cohort studies using advanced methods to control for confounding were considered by experts and informed treatment guidelines (68,80).…”
Section: Body Of Evidence Evolving Over Timementioning
confidence: 99%
“…Unmeasured confounders and residual confounding may lead to incorrect conclusions (85). Further points of criticism comprise poor quality of study reporting according to the guidelines of reporting observational studies [STROBE; (86)], or failure to include key clinical endpoints such as mortality or hospitalization duration as primary endpoints (87). Only large cohort studies using advanced methods to control for confounding were considered by experts and informed treatment guidelines (68,80).…”
Section: Body Of Evidence Evolving Over Timementioning
confidence: 99%
“…High-quality evidence is always important, particularly in the context of a pandemic ( Raynaud et al, 2021 ). Evidence is emerging that many COVID-19 trials are of poor quality: reviews of registered COVID-19 trials (as opposed to fully published studies) have revealed that many are not blinded and have many other features associated with poor quality ( Jung et al, 2021 ;Karlsen et al, 2020 ;Mainoli et al, 2021 ;Mehta et al, 2020 ;Pundi et al, 2020 ;Zhu et al, 2020 ). Additionally, there is evidence that many studies of traditional Chinese medicine for COVID-19 are also at risk of bias Gao et al, 2021 ), and where risk of bias has been investigated in the context of specific treatments (e.g., hydroxychloroquine), concerns have been raised of the lack of high-quality studies ( Mazhar et al, 2020 ).…”
Section: Research In Contextmentioning
confidence: 99%
“…Сама отчетность зачастую скудна, выводы исследований и клинических испытаний, которые важны для пациентов и ЛПУ, не раскрыты. Например, 61,4% протоколов исследований не сообщили, были ли включены в исследование пациенты с риском смерти -они не были приоритетными в клинических испытаниях, среди которых лишь 11,4% завершились (на 19.04.2020) [5]. Как известно, чем меньше размер выборки, тем выше риск не обнаружить побочные эффекты, которые, несмотря на незначительную частоту, играют огромную роль в изучении фармакодинамики препаратов.…”
Section: проблемы проведения исследований и клинических испытанийunclassified